EXPERIMENTAL HYPOTHYROIDISM INDUCE INCREASED EXPOSURE OF αLFuc, βDGal AND DGalNAc CARBOHYDRATE DETERMINANTS IN RAT ADRENAL GLANDS - Lutsyk, S.A.; Yashchenko, A.M. (World of Medicine and Biology, 2012)
A set of eight lectins with different carbohydrate affinities (LCA, LABA, SNA, RCA, WGA, PNA, SBA, and HPA) was used for the investigation of rat adrenal gland glycoconjugate remodeling under the influence of experimental hypothyroidism, induced with 5 mg/kg of antithyroid drug mercazolil, added daily to rat food allowance during 30 days. Сarbohydrate determinants, labelled with lectin-perxidase conjugates, were visualized with diaminobenzidine. Hypothyroidism induced enhancement of αLFuc, βDGal, and DGalNAc determinants exposure as detected by increased LABA, PNA, and SBA binding. Particularly, in control rats LABA reactivity was restricted to vascular endothelium of adrenal medulla, while under experimental conditions this same lectin strongly labelled also vascular endothelium of adrenal cortex. Under hypothyroidism PNA reactivity of zona glomerulosa cells increased significantly. PNA and SBA visualized characteristic spider-like structures of adrenal cortex and medulla, apparently representing secretory granules, retained by plasma membranes of adjacent hormone-producing cells. These data encompass significant influence of hypothyroidism on glycoconjugate processing in adrenal gland; lectin LABA can be recommended as selective histochemical marker of the rat adrenal gland vascular endothelium.
Keywords: adrenal gland; rat; experimental hypothyroidism; lectins